Kakkonto Inhibits Cytokine Production Induced by Rhinovirus Infection in Primary Cultures of Human Nasal Epithelial Cells - Saito, Natsumi; Kikuchi, Akiko; Yamaya, Mutsuo; Deng, Xue; Sugawara, Mitsuru; Takayama, Shin; Nagatomi, Ryoichi; Ishii, Tadashi (Frontiers in Pharmacology, 2021)
Rhinovirus (RV) is a primary etiologic agent of common cold that can subsequently acutely exacerbate bronchial asthma or chronic obstructive pulmonary disease. Kakkonto (Ge-gen-tang in Chinese), one of the most frequently prescribed traditional Japanese (Kampo) medicines, is used for treating common cold, shoulder stiffness, or inflammatory diseases of the upper body. Previous experimental studies have indicated that kakkonto exerts antiviral and anti-inflammatory effects on the influenza virus and the human respiratory syncytial virus. However, there is a lack of reports investigating the efficacy of kakkonto in RV infection. Hence, the aim of the current study was to investigate the effects of kakkonto on RV infection of human nasal epithelial (HNE) cells. HNE cells obtained via endoscopic sinus surgery were cultured and infected with RV14, with or without kakkonto treatment. The supernatants from the cells were collected, and the RV14 titer and cytokine levels were assessed. Reverse transcription-polymerase chain reaction was performed to determine the amount of viral RNA, while the level of nuclear factor kappa B (NF-κB) subunits in the nucleus was assessed by enzyme-linked immunosorbent assay. Although kakkonto treatment did not reduce RV14 titer or RNA levels, indicating that it did not inhibit RV14 proliferation, it was found to reduce the production of specific pro-inflammatory cytokines, including interleukin (IL)-8, tumor necrosis factor (TNF)-α, and monocyte chemotactic protein-1 (MCP-1). Unlike that observed with the kakkonto extract, none of the crude drugs containing kakkonto reduced IL-8 level. Furthermore, though kakkonto treatment significantly reduced p50 levels, it did not impact the p65 subunit of NF-κB. These results indicated that kakkonto can inhibit inflammation caused by RV infection and may exert an immunomodulatory effect on HNE cells. This is the first report to elucidate the effects of kakkonto extract on RV infection in primary cultures of HNE cells, providing evidence that kakkonto may act as an effective therapy for RV infection and subsequent airway inflammation.